Clinical-economic evaluation of distance education and blood glucose level monitoring in adults with diabetes mellitus - Omelyanovskiy, V. V.; Fediaeva, V. K. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2024)
Background. Health Technology Assessment (HTA) in the Russian Federation has been performed for drugs, not for other medical technologies, which leads to decision making difficulties today. Aim. This study aimed to assess the clinical and economic efficiency of distance education and monitoring of blood glucose levels in patients with diabetes mellitus (DM) of both types. Materials and methods. The HTA was prepared using Markov model with a cost-effectiveness analysis methodology. The number of DM complications depending on glycated hemoglobin level with distance education and blood glucose level and without, that has been used for modeling cost of distance education and blood glucose monitoring as well as cost of drugs’ therapy and hospital admission due to DM complications with methodology and source of Obligatory Medical Insurance Fund on 30-yy horizon of modeling. Results. Distance education and blood glucose monitoring in DM patients leads to decrease in complication level as well as mortality, and acceptable additional financial costs from the 5th year of modeling for DM type 1 and from the 6thyear of modeling for type 2 without insulin dose changing. Conclusion. Clinical-economic reasonability of distance education and DM patients’ monitoring are demonstrated in this work. These results should be considered in the decision-making process for HTA budget financing.